Keefektifan Model Pembelajaran Make A Match dan Card Sort Ditinjau dari Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di Kelas VIII SMP Negeri 10 Padang - Ruri Albersa; Remiswal; Rozi Fitriza (Irfani, 2026)
This study was motivated by the low level of student participation and learning outcomes in Islamic Religious Education and Character (PAIBP) among eighth-grade students at SMP Negeri 10 Padang, particularly in the Islamic Cultural History component on Muslim scholars during the Abbasid Dynasty. The research aimed to analyze the improvement in learning outcomes and to compare the effectiveness of the Make a Match and Card Sort cooperative learning models assisted by comic media. The study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The sample consisted of two experimental classes: Experiment 1 implemented the Make a Match model, while Experiment 2 applied the Card Sort model. Data were collected through objective pre-test and post-test instruments and analyzed using Paired Sample T-Test, Independent Sample T-Test, and N-Gain analysis with SPSS version 23. The findings revealed that both models significantly improved students’ learning outcomes (Sig. 0.000 < 0.05). However, a significant difference was found between the two classes (Sig. 0.047 < 0.05), with the Card Sort class achieving a higher post-test mean score (85.47) compared to the Make a Match class (81.06). The N-Gain results for both groups were in the moderate category, with Card Sort showing slightly higher effectiveness. These results indicate that while both cooperative models are effective, Card Sort is relatively more effective for factual and conceptual materials due to its emphasis on systematic classification and conceptual organization.